2001
DOI: 10.1093/jexbot/52.360.1555
|View full text |Cite
|
Sign up to set email alerts
|

Possible explanation of the disparity between the in vitro and in vivo measurements of Rubisco activity: a study in loblolly pine grown in elevated pCO2

Abstract: Rubisco activity can be measured using gas exchange (in vivo) or using in vitro methods. Commonly in vitro methods yield activities that are less than those obtained in vivo. Rubisco activity was measured both in vivo and in vitro using a spectrophotometric technique in mature Pinus taeda L. (loblolly pine) trees grown using free-air CO2 enrichment in elevated (56 Pa) and current (36 Pa) pCO2. In addition, for studies where both in vivo and in vitro values of Rubisco activity were reported net CO2 uptake rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
3
27
1
1
Order By: Relevance
“…A closer match to in vitro enzyme activity of Rubisco can be obtained by considering the mesophyll conductance to CO 2 to the site of carboxylation (Rogers et al, 2001;Flexas et al, 2007); however, as g m values are available for so few of the sampled species, we assumed that C i is equal to C c , the CO 2 concentration at the chloroplast. The C i at which photosynthesis is colimited by both carboxylation and RuBP regeneration was calculated for each A-C i curve based on the apparent V cmax , J max and R day using the C 3 photosynthesis model.…”
Section: Datasetsmentioning
confidence: 99%
“…A closer match to in vitro enzyme activity of Rubisco can be obtained by considering the mesophyll conductance to CO 2 to the site of carboxylation (Rogers et al, 2001;Flexas et al, 2007); however, as g m values are available for so few of the sampled species, we assumed that C i is equal to C c , the CO 2 concentration at the chloroplast. The C i at which photosynthesis is colimited by both carboxylation and RuBP regeneration was calculated for each A-C i curve based on the apparent V cmax , J max and R day using the C 3 photosynthesis model.…”
Section: Datasetsmentioning
confidence: 99%
“…Besides, the great problem in RuBPCO activity assay in vitro is a low solubility of RuBPCO enzyme. Rogers et al (2001) showed that only 33 % of RuBPCO got into supernatant (or into filtration) during the extraction from the leaf. That is another reason why values V Cmax that express RuBPCO activity in vivo are higher than values of RuBPCO activity obtained in vitro; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Then the mixture was centrifuged at 15 000 g for 10 min at 48C. The supernatant which was used to analyze RuBisCo activity was collected and measured by spectrophotometer at 340 nm using UV-1601 spectrophotometer (Rogers et al 2001). All statistical analyses were performed using trend analysis by SPSS v.11.5 (SPSS Inc., Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%